2022
DOI: 10.1155/2022/6187912
|View full text |Cite
|
Sign up to set email alerts
|

Induction Machine Bearing Fault Detection Using Empirical Wavelet Transform

Abstract: The detection of faults related to the optimal condition of induction motors is an important task to avoid the malfunction or loss of the motor, thus avoiding high repair or replacement costs and faults in the efficiency of the process to which they belong. These faults are not limited to a single area; mechanical and electrical problems can cause a fault. Specifically, the bearing of a motor is subjected to several effects that cause bearing faults, which cause significant breakdowns in the machinery. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similarly, Lopez-Gutierrez et al proposed to apply an empirical wavelet transform to the vibration signal of an IM to enhance bearing fault detection. The method is able to extract a series of amplitudes and frequencies and obtain the Fourier spectrum for further analysis [23]. Agah et al proposed a hybrid method based on stator current signals for rotor rod fracture and rotor mixed eccentricity faults of three-phase squirrel cage asynchronous motors.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lopez-Gutierrez et al proposed to apply an empirical wavelet transform to the vibration signal of an IM to enhance bearing fault detection. The method is able to extract a series of amplitudes and frequencies and obtain the Fourier spectrum for further analysis [23]. Agah et al proposed a hybrid method based on stator current signals for rotor rod fracture and rotor mixed eccentricity faults of three-phase squirrel cage asynchronous motors.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that the novel method extracted the bearing fault features successfully. Lopez et al [14] suggested an empirical wavelet transform (EWT)-based methodology for detecting bearing faults. The experimental results revealed that the proposed technique efficient in diagnosing induction motor-bearing defects.…”
Section: Introductionmentioning
confidence: 99%